2023
DOI: 10.1038/s41467-023-38457-x
|View full text |Cite
|
Sign up to set email alerts
|

saRNA vaccine expressing membrane-anchored RBD elicits broad and durable immunity against SARS-CoV-2 variants of concern

Abstract: Several vaccines have been widely used to counteract the global pandemic caused by SARS-CoV-2. However, due to the rapid emergence of SARS-CoV-2 variants of concern (VOCs), further development of vaccines that confer broad and longer-lasting protection against emerging VOCs are needed. Here, we report the immunological characteristics of a self-amplifying RNA (saRNA) vaccine expressing the SARS-CoV-2 Spike (S) receptor binding domain (RBD), which is membrane-anchored by fusing with an N-terminal signal sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…9,10 A novel COVID-19 vaccine, VLPCOV-01, was developed using the LNP-encapsulated saRNA platform derived from an alphavirus amplification system that encodes replicase and transcriptase functions comprising the alphavirus nonstructural proteins (nsp1-4) from the attenuated TC-83 strain of Venezuelan equine encephalitis virus (VEEV), and which expresses a membrane-anchored receptor-binding domain (RBD). 11,12 When delivered as a booster vaccine in the phase 1 VLPCOV-01-0102 clinical trial, VLPCOV-01 induced strong and persistent immune responses in both non-elderly and elderly healthy participants who had received primary vaccination with BNT162b2; neutralizing antibody titers to Wuhan, Delta, and Omicron variants of SARS-CoV-2 were observed. 11 The immune response achieved was comparable to that observed with BNT162b2 and with a similar safety profile, but at one-tenth of the vaccine dose.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 A novel COVID-19 vaccine, VLPCOV-01, was developed using the LNP-encapsulated saRNA platform derived from an alphavirus amplification system that encodes replicase and transcriptase functions comprising the alphavirus nonstructural proteins (nsp1-4) from the attenuated TC-83 strain of Venezuelan equine encephalitis virus (VEEV), and which expresses a membrane-anchored receptor-binding domain (RBD). 11,12 When delivered as a booster vaccine in the phase 1 VLPCOV-01-0102 clinical trial, VLPCOV-01 induced strong and persistent immune responses in both non-elderly and elderly healthy participants who had received primary vaccination with BNT162b2; neutralizing antibody titers to Wuhan, Delta, and Omicron variants of SARS-CoV-2 were observed. 11 The immune response achieved was comparable to that observed with BNT162b2 and with a similar safety profile, but at one-tenth of the vaccine dose.…”
Section: Introductionmentioning
confidence: 99%
“…This vector expresses the VEEV replication machinery to replicate and transcribe the saRNA, resulting in efficient expression of the gene(s) of interest. Due to this self-amplification process, the level and duration of expression of target antigens are expected to be higher and more durable than that observed with nonreplicating mRNA vaccine platforms 10 . One clinical trial using an saRNA vector expressing the whole SARS S protein demonstrated that 5 µg of the saRNA induced significant amounts of neutralizing antibodies 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the absorbance measurement of blue TMB ox1 catalyzed by HRP is strongly time-dependent, leading to unreliable readout in practical applications. To address this problem, a terminator, typically a strong acid, is generally required, which unfortunately not only compromises sensing accuracy but also causes safety hazards in bioassays. ,, Therefore, selective catalytic oxidation of TMB via a direct two-electron pathway is highly envisioned but challenging because of the thermodynamically favorable complexation between TMB ox2 and unreacted TMB back to TMB ox1 .…”
Section: Introductionmentioning
confidence: 99%
“…Precise regulation of chemical reaction processes helps to realize controllable chemical synthesis with high selectivity and efficiency. As a typical substrate and chromogenic probe, 3,3′,5,5′-tetramethylbenzidine (TMB) features particular interest, due to its low toxicity and high sensitivity of response. Meanwhile, horseradish peroxidase (HRP) has been widely used in immunochemistry due to its high catalytic efficiency and specificity under mild reaction conditions. Along this line, HRP-H 2 O 2 -TMB has become the standard chromogenic system in the well-known clinical enzyme-linked immunosorbent assay (ELISA), which generally detects the absorbance of the one-electron oxidation product of TMB (TMB ox1 ). Notably, TMB ox1 is essentially a blue charge-transfer complex, consisting of the parent diamine (TMB) and the two-electron oxidation product of diimine (TMB ox2 ) in rapid thermodynamical equilibrium with a radical cation (Figure a) . After all free TMB is completely oxidized in bulk solution, blue TMB ox1 undergoes one more electron oxidation into the final stable yellow product (TMB ox2 ).…”
Section: Introductionmentioning
confidence: 99%